2022
DOI: 10.1002/jmv.27890
|View full text |Cite
|
Sign up to set email alerts
|

Are we ready for long‐acting? A feasibility evaluation of long‐acting cabotegravir–rilpivirine in clinical practice

Abstract: Cabotegravir and rilpivirine are the first drugs to be approved as injectable therapy to treat individuals with HIV. Despite encouraging results, the guidelines specify strict criteria for eligibility that could limit the feasibility of this strategy. We collected the clinical data of HIV-positive patients who were being treated at a single, third-level center in Italy. All patients were on stable therapy and showed suppressed viral load on their most recent analyses. We performed a cross-sectional analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…It is possible that the strict eligibility criteria for LAI initiation is also creating barriers. Previously, it has been found that resistance to rilpivirine, strict VS criteria, and hepatitis B coinfection were limitations to uptake [ 27 , 29 , 30 ]. A previous study in California found that of 15 patients who initiated LAI with a detectable viral load, 12 achieved VS [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the strict eligibility criteria for LAI initiation is also creating barriers. Previously, it has been found that resistance to rilpivirine, strict VS criteria, and hepatitis B coinfection were limitations to uptake [ 27 , 29 , 30 ]. A previous study in California found that of 15 patients who initiated LAI with a detectable viral load, 12 achieved VS [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The propensity for long-acting cabotegravir and rilpivirine every 2 months among HIV-infected people eligible for treatment Dear Editor, Borghetti and coll. 1 recently evaluated the proportion of individuals who could be eligible for switching to a long-acting (LA) regimen with cabotegravir and rilpivirine.…”
mentioning
confidence: 99%